A novel amperometric catechol biosensor based on α-Fe2O3 nanocrystals-modified carbon paste electrode. (3rd April 2017) - Sarika, C.; Shivakumar, M. S.; Shivakumara, C.; Krishnamurthy, G.; Narasimha Murthy, B.; Lekshmi, I. C.
Abstract: In this work, we designed an amperometric catechol biosensor based on α-Fe2 O3 nanocrystals (NCs) incorporated carbon-paste electrode. Laccase enzyme is then assembled onto the modified electrode surface to form a nanobiocomposite enhancing the electron transfer reactions at the enzyme's active metal centers for catechol oxidation. The biosensor gave good sensitivity with a linear detection response in the range of 8–800 μM with limit of detection 4.28 μM. We successfully employed the sensor for real water sample analysis. The results illustrate that the metal oxide NCs have enormous potential in the construction of biosensors for sensitive determination of phenol derivatives.